2020
DOI: 10.1155/2020/9526790
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Peripheral Arterial Blood Flow Using Peri-Interventional Fluoroscopic Parameters: An In Vivo Study Evaluating Feasibility and Clinical Utility

Abstract: Purpose. The purpose of this study was to evaluate various objective, quantitative, time-resolved fluoroscopic imaging parameters for use in the peri-interventional evaluation of stenotic peripheral arterial disease lesions. Material and Methods. Ten patients (median age, 64; age range, 52 to 79; 8 males, 2 females) with high-grade stenoses of either the superficial femoral or popliteal arteries who underwent endovascular treatment were included. During each intervention, two series of intraprocedural fluorosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The relative change from baseline is larger in qDSA (9.0% reduction in blood velocity per mL of embolic particles delivered) than in ccDSA (1.5% increase in TTP per mL of embolic particles delivered) scans. Previous studies have shown the utility of quantitative fluoroscopy, although those techniques suffer from many of the same limitations as ccDSA [22]. qDSA may feasibly be performed using fluoroscopy, as long as there is sufficient signal in the image to identify peaks in the TAC and there is sufficient temporal resolution to sample the signal.…”
Section: Discussionmentioning
confidence: 99%
“…The relative change from baseline is larger in qDSA (9.0% reduction in blood velocity per mL of embolic particles delivered) than in ccDSA (1.5% increase in TTP per mL of embolic particles delivered) scans. Previous studies have shown the utility of quantitative fluoroscopy, although those techniques suffer from many of the same limitations as ccDSA [22]. qDSA may feasibly be performed using fluoroscopy, as long as there is sufficient signal in the image to identify peaks in the TAC and there is sufficient temporal resolution to sample the signal.…”
Section: Discussionmentioning
confidence: 99%
“…Digital subtraction angiography (DSA) is widely regarded as the diagnostic reference standard primarily because dynamic flow information is reliably obtained 3 …”
mentioning
confidence: 99%
“…1,2 Digital subtraction angiography (DSA) is widely regarded as the diagnostic reference standard primarily because dynamic flow information is reliably obtained. 3 However, its invasiveness and cost, as well as its requirement for ionizing radiation, have led to the development of MR-angiography (MRA) as an alternative, either as a multistation contrast-enhanced (ce) MRA or as a timeresolved (TR) MRA. MRA has high diagnostic accuracy and is often considered as the imaging modality of choice.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) angiography (MRA) appears as an appealing alternative, either as an MRI with multi‐station contrast enhancement (CE) or as time resolution (TR) MRA. Indeed, MRA has high diagnostic accuracy and has been recently proposed as the imaging modality of choice 1–6 …”
mentioning
confidence: 99%
“…Indeed, MRA has high diagnostic accuracy and has been recently proposed as the imaging modality of choice. [1][2][3][4][5][6] In this issue of the journal, the authors used DSA to evaluate the diagnostic accuracy of time-resolved 4D MRA with interleaved stochastic trajectories (TWIST-MRA) by using maximum intensity projections (MIPs) of dynamic images acquired with reduced doses of contrast agent. Analyzing 14 patients with a total of 256 artery segments, a high diagnostic performance was achieved for detecting >50% stenosis with a sensitivity and specificity of 92.9% and 98.5%, respectively, and detecting artery occlusion with a sensitivity and specificity of 93.1% and 99.1%, respectively.…”
mentioning
confidence: 99%